Research Progress on Chitinase and Chitosanase with Transglycosylation Activity - Yingying WEI; Minjuan GUI; Huihui SUN; Ling ZHAO; Rong CAO (Shipin gongye ke-ji, 2025)
N−acetyl chitooligosaccharides and chitooligosaccharides with high degree of polymerization are highly valued for their superior bioactivities. However, traditional preparation methods face various limitations, such as uncontrollable processes and challenges inseparation and purification. Recent studies have discovered that certain chitinases and chitosanases possess both hydrolysis and transglycosylation (TG) activities. The TG reaction offers advantages in producing oligosaccharides with high-degree polymerization, including easy accessibility to substrates and low production costs. This paper reviews recent advances in chitinases and chitosanases with TG activity, analyzes the key amino acid residues affecting TG activity in chitinases, and discusses the impact of molecular modifications of these key residues on TG activity. The goal is to provide insights for further research on chitinases and chitosanases with TG activity and their subsequent development and utilization, thereby promoting the green production and industrialization of oligosaccharides with high-degree polymerization.